Interrelation of Religion and Culture: An Analysis of Honoring Asyhur Al-Hurum Culture on Cliford Greetz's Anthropological Theory - Naylul Izzah Walkaromah; Siti Khomairoh (Pascasarjana IAIN Metro, 2024)
Religion and culture are two interconnected entities. However, there are some groups who claimed that Islam is against local culture and traditions. That arguments are significant to be reviewed and studied comprehensively. This research aims to review the interrelation between Islamic teachings and the culture of honoring asyhur al-hurum from the perspective of Clifford Geertz's anthropological theory. With a library research approach and qualitative method, this research results that the teachings in Islam appreciate and are accommodative of local traditions. Many pre-Islamic traditions have been adopted and then integrated into Islam, one of them is the culture of honoring asyhur al-hurum (Rajab, Dhulqa'dah, Dhulhijjah, and Muharram). There are several verses of the Qur'an that contain an appreciative attitude towards this culture, including QS al-Baqarah verses 194, 197, and 217; QS al-Maidah verses 2 and 97; QS al-Taubah verse 36. Some of the verses mentioned provide an understanding that Islam is a religion that strengthens respect for the culture of the glory of the haram months (asyhur al-hurum). The verse reflects the tahmil process as a form of dialectic between the Qur'an and culture. Based on the analysis using Clifford Geertz's theory of models for reality and models of reality, the teachings in Islam instruct Muslims to glorify the haram months by increasing worship, both ritual worship and social worship related to cultural practices that apply in a multicultural society. The interrelation between religious teachings about the haram months and local culture contributes to the formation of collective identity, both in religious and social contexts.